127 Echocardiographic changes following active heat acclimation. (17th July 2020) - Parsons, Iain; Snape, Daniel; O'Hara, John; Holdsworth, David; Stacey, Michael; Gall, Nick; Chowienczyk, Phil; Wainwright, Barney; Woods, David
Abstract : Introduction: Thermoregulatory induced cardiovascular insufficiency impairs the ability to exercise in the heat. Heat adaption through acclimatisation or acclimation (HA) improves cardiovascular stability by maintaining cardiac output, despite lowering resting heart rate, due to compensatory increases in left ventricular stroke volume. The primary aim of this study was to assess whether 2D transthoracic echocardiography (TTE) could be used to confirm differences in resting cardiovascular responses, before and after isothermic HA. Methods: Thirteen male endurance trained cyclists underwent a resting blinded TTE before and after randomisation to either 5 consecutive daily exertional heat exposures of controlled hyperthermia at 32°C with 70% relative humidity (RH) (HOT) or 5-days of exercise in temperate (21°C with 36% RH) environmental conditions (TEMP). Measures of HA included heart rate, gastrointestinal temperature, skin temperature, sweat loss, total non-urinary fluid loss (TNUFL), plasma volume and participant's ratings of perceived exertion (RPE). Results: Following HA, the HOT group demonstrated increased sweat loss (p=0.01) and TNUFL (p=0.01) in comparison to the TEMP group with a significantly decreased RPE (p=0.01). On TTE, post exposure, there was a significant comparative increase in the HOT group in left ventricular end diastolic volume (p=0.029), SV (p=0.009), left atrial volume (p=0.025), inferior vena cava diameter (p=0.041), and a significant difference in mean peak diastolic mitral annular velocity (e') (p=0.044). Conclusions: The significant differences in thermal comfort, sweat loss and TNUFL following the active HA in the HOT group are confirmatory for heat adaptation. Overall, these data demonstrate several concurrent cardiovascular adaptations occurring in response to HA, with the cardinal adaptation probably being that of increased preload driven by an increased plasma volume, in conjunction with enhanced ventricular compliance. Greater cardiac relaxation is likely to reflect cellular adaptations in the myocardium. Echocardiography is a useful tool to demonstrate and quantify cardiac adaptation to heat. This has several implications to utilise TTE as a research tool in elite athletes firefighters, miners, the military or aid workers particularly in the development of tailored rapid HA regimes. Conflict of Interest: None